Lived Experiences of the COVID-19 Pandemic Among the Vietnamese Population in the Region of Peel - Cao, Tiffany; Rishworth, Andrea; Wilson, Kathi; Ali, Fatema; Gallaway, Tracey (Journal of racial and ethnic health disparities, 2024)
Racial discrimination towards Southeast Asian populations is a longstanding issue in Canada which has intensified during the COVID-19 pandemic. Although extensive work demonstrates inequities among Southeast Asian communities during the pandemic, much work categorizes Asians as one homogenous population neglecting the unique experiences of different Asian subgroups along with the ways COVID-19 differentially affects Southeast Asians. To attend to population variations, this paper explores the lived experiences among Vietnamese individuals during the pandemic in the Peel Region of Ontario Canada. Specifically, this paper examines social and economic impacts of COVID-19, access to healthcare services and vaccines, sources of vaccine information, and impacts of COVID-19 related discrimination among young and older adults. Drawing on in-depth interviews with young and older adults ( n =6:8) the results reveal important social and economic impacts created by COVID-19 that vary across generations and impact health and wellbeing. These impacts are challenged further by barriers to healthcare access which were compounded by intersecting inequities experienced among Vietnamese immigrants in the Peel Region. While vaccine hesitancy was not a main concern, the findings demonstrate important generational differences with respect to commonly used and trusted information related to historical events and social media use. Although racial discrimination was a dominant concern, younger participants did not feel unsafe but expressed concern for the safety of their older family members and friends. The study underscores the need to consider historical dynamics and the ways they shape government opinions and trust, experiences of racial discrimination and socio-economic realities among racialized, immigrant populations.